Priority species of bamboo and rattan - Rao, A.N.; Ramanatha Rao, V.; Williams, J.T.; International Plant Genetic Resources Institute; International Network for Bamboo and Rattan (1998)
This publication describes a limited number of species of bamboo and rattan selected from the several hundred in existence for priority research and development; the background details, criteria for selection of species, the major priority bamboo and rattan species selected and notes on each one are given, compiled with the assistance of experts in the fields of bamboo and rattan taxonomy, ethnobotany, silviculture, conservation and genetics.